INFLUENCE OF VARIOUS PHOSPHATIC SOURCES ON YIELD AND YIELD COMPONENTS OF WHEAT - BANERJEE, MAHUA; RAI, R.K. (Annals of Agricultural Research, 2014)
Field experiment was conducted during rabi season of 2002-03 and 2003-04 at Indian Agricultural Research Institute, New Delhi to see the response of various phosphatic sources in the form of chemical fertilizers and biofertilizers on yield and yield components of wheat (cv. HD 2285). The field experiment was conducted in randomized block design. There were twelve treatments with various phosphatic sources applied singly or in combination with nitrogen. All these treatments were replicated thrice. The yield components of wheat crop were favourably affected by N120 SSP30 VAM in 2002-03 and by N120 RP30 PSB in 2003-04. In wheat, the highest grain yield of 59.56 q/ha was recorded in treatment N120 SSP30 VAM in 2002-03, and in 2003-04 the highest value of 60.32 q/ha was observed in N120 RP30 PSB.